Meningkatkan Minat UMKM Melalui Penyediaan Akses Permodalan Dan Bantuan Teknis Di Sidrap - Rusdi, Muhammad; Palla, Rahmat Anggung; Niswar, Muh.; Zainuddin, Akmal; Maulia, Umrah Mekar (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The aim of this research is to increase the interest of MSMEs in Sidrap in accessing capital and technical assistance. First, this research analyzes barriers to access to capital and finds solutions to these problems. Second, this research assesses the need for technical assistance by identifying the specific needs of MSMEs in Sidrap to increase their capacity and competitiveness. Fourth, this research develops a targeted technical assistance program to help the growth of small and medium enterprises (MSMEs) in Sidrap. Finally, this research provides policy suggestions that can be used by local governments and other stakeholders to support small and medium enterprises (MSMEs). It is hoped that through this comprehensive approach, MSMEs in Sidrap can increase their competitiveness and increase their contribution to the local economy by gaining better access to capital and technical assistance that suits their needs. In addition, this research will serve as a basis for more efficient policy making that supports the development of MSMEs in Sidrap.